Design of Programmable LED Based Phototherapy System. (2nd June 2019) - Kohli, Himani; Srivastava, Sangeeta; Sharma, Sanjeev Kumar; Chouhan, Satish; Oza, Manan
Abstract : Light based systems are frequently used in the field of medicine for diagnostic and surgical procedures, medical photography, phototherapy, etc. Phototherapy involves the use of light energy for the treatment of physical or mental illnesses. Illumination parameters such as wavelength and dose of therapy can be varied to have distinct effects on cells and tissues. This has necessitated the need to design a system which is programmable for various parameters related to therapy and can also be used by people at large for biomedical applications. The paper presents the design and implementation of a portable, hand-held and programmable Light Emitting Diode (LED) based phototherapy system using embedded technology. The system is designed around the ARM based TM4C123GH6PM microcontroller processor. The microcontroller has been programmed to allow for selection of various parameters such as frequency, duty cycle, and time of exposure. The matrix keypad interface and liquid crystal display (LCD) offer the ease of human interface. An LED driver circuit has been efficiently designed to modulate the output power of LED. Further, Super Bright LED (SLED) of wavelength~ 633 nm has been successfully tested and results of optical characterization including spectral and spatial response have been presented in the results section. The designed system successfully achieves the programmable parameters required for dose optimisation required for enhancing the therapeutic effects of a phototherapy system.